Repository management: an emerging profession in the information sector - Wickham, Jackie (2010)
The first half of the 21st century has seen huge growth in the open access movement with the potential to change the nature of scholarly communication. Higher education institutions in the United Kingdom have established institutional repositories to showcase the research output of their academic staff. The responsibility for leading this work has been taken up by libraries and this has created a new role in the profession; that of repository manager. Traditional library skills and knowledge are required (e.g. cataloguing, digital asset management) but this needs to be supplemented by new skills such as advocacy and knowledge of research methods and funding systems.